Activation of the methylreductase system from Methanobacterium bryantii by ATP. - Whitman, W B (1983)
The methylreductase of Methanobacterium bryantii required ATP for activity. There was sufficient ATP synthesis in extracts to account for the observed activity. Hexokinase inhibited the methylreductase by competing for endogenously synthesized ATP. The uncoupler, carbonyl cyanide p-trifluoromethyoxyphenyl hydrazone, inhibited only at concentrations greater than 0.5 mM, and detergents and non-halogenated membrane-permeable-ions did not inhibit. Thus, membrane proton gradients are not important in activation. In addition, maximal activation was obtained with less than 0.25 mM ATP, was inhibited by beta, gamma-imido ATP, and was strongly temperature dependent. The activated state was very unstable, having a half-life of 5 to 15 min. After gel filtration at 5 degrees C, the methylreductase retained partial activity for a short time in the absence of ATP. These observations indicate that activation involves the modification of a protein or protein-bound cofactor of the methylreductase system.